Uma proposta de metodologia de engenharia de custos adequada à realidade brasileira: uma pesquisa quali e quanti no setor de construção civil - Gabriele, Pedrita Dantas (2011)
The Brazilian industry is facing rapid growth and the consequent reduction of its level of control, in particular, the cost control. This fact, combined with an historical extrapolation of planned cost in comparison to real project costs, and with few specific studies in the area of cost management focused on the Brazilian reality, cost management became a differential to obtain competitive advantage. Thus, this paper has as main objective the development of a methodology for cost management tailored to the specific environment in which the Brazilian industry is located, titled CPT Methodology . For this, we performed a literature search of national and international references on cost management, and also quantitative and qualitative applied research, which were consulted 22 professionals working in this research. In the end, we analyzed the application of the methodology developed in the context of the construction industry. Finally, we emphasize that the resulting methodology of this dissertation is a guide applicable to any industry, however, do not constitute a step by step to its immediate implementation. For this to occur, it is necessary that the methodology is adapted to the reality of the sector in which it operates, through expert analysis.